2015
DOI: 10.1200/jco.2013.54.9386
|View full text |Cite
|
Sign up to set email alerts
|

BREATH: Web-Based Self-Management for Psychological Adjustment After Primary Breast Cancer—Results of a Multicenter Randomized Controlled Trial

Abstract: Purpose Early breast cancer survivors (BCSs) report high unmet care needs, and easily accessible care is not routinely available for this growing population. The Breast Cancer E-Health (BREATH) trial is a Web-based self-management intervention to support the psychological adjustment of women after primary treatment, by reducing distress and improving empowerment. Patients and Methods This multicenter, randomized, controlled, parallel-group trial evaluated whether care as usual (CAU) plus BREATH is superior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
289
1
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 175 publications
(309 citation statements)
references
References 60 publications
4
289
1
15
Order By: Relevance
“…There was a wide range of levels of empowerment, indicating room for improvement. Empowerment levels in the current study were comparable to those in a previous study in patients with breast cancer; however, this study only included female patients who were older than patients in the current study sample 21. The results of the current study demonstrated that the most important factors associated with empowerment in AYA patients were autonomy, sex, social support and coping.…”
Section: Discussionsupporting
confidence: 74%
“…There was a wide range of levels of empowerment, indicating room for improvement. Empowerment levels in the current study were comparable to those in a previous study in patients with breast cancer; however, this study only included female patients who were older than patients in the current study sample 21. The results of the current study demonstrated that the most important factors associated with empowerment in AYA patients were autonomy, sex, social support and coping.…”
Section: Discussionsupporting
confidence: 74%
“…Our BREATH RCT of a low‐intensity online CBT‐based self‐management intervention for breast cancer survivors used clinic‐based consecutive sampling 6. RCT participants were a representative clinic sample with 68% reporting low‐medium distress.…”
Section: Self‐referral Recruitmentmentioning
confidence: 99%
“…Our experience of using self‐referral recruitment in 2 RCTs8, 9 has resulted in relatively short inclusion periods, attainment of target recruitment, and high participation rates relative to our other RCTs not using self‐referral as a recruitment strategy6, 10, 11, 12 (see Table 1). This provides preliminary support for the feasibility of self‐referral in POI RCTs.…”
Section: Is Self‐referral Feasible In Poi Rcts?mentioning
confidence: 99%
“…While reports of online interventions for cancer report on overall uptake (e.g. [7][8][9]), little research examines characteristics that predict uptake.…”
mentioning
confidence: 99%
“…Barriers to accessing therapist-based interventions include limited availability [3], travel distances [4], reluctance to disclose distress [3], and concerns about stigma [3]. In response, online self-help interventions are being increasingly explored [5][6][7][8][9].…”
mentioning
confidence: 99%